2018
DOI: 10.21767/2471-8548.10010
|View full text |Cite
|
Sign up to set email alerts
|

Cell Transplantation: A Novel Therapeutic Modality for Cerebral Palsy with Co-Morbid Intellectual Disability

Abstract: Background: Cerebral palsy (CP) is a non-progressive disorder. The global incidence of neonatal CP is 1-5 per 1000 live births where 45% of children with CP have a comorbid intellectual disability (ID). This affects the quality of life and reduces life expectancy of affected individuals. Methods and findings:With an aim to study the efficacy and safety of autologous bone marrow mononuclear cells (BMMNCs) transplantation in CP with ID, we administered a 17-year-old boy with BMMNCs along with neurorehabilitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 32 publications
0
2
0
4
Order By: Relevance
“…UCBs and peripheral blood mononuclear cell infusion therapy for patients with CP improved brain glucose metabolism, as observed in PET studies 73 , 80 . Autologous BM-MNC therapies for patients with ASD also showed improvements in glucose metabolism and various cognitive and behavioral symptoms such as eye contact, attention and concentration, hyperactivity, sitting tolerance, social interaction, stereotypical behavior, aggressiveness, communication, speech, command following, and self-stimulatory behavior, as well as improvement of glucose metabolism and motor function in patients with CP 47 , 81 . In 2020, we reported that angiogenesis is activated by BM-MNCs via gap junction–mediated cell–cell interaction soon after cell transplantation and that cell–cell interaction via gap junctions is the prominent pathway for the activation of angiogenesis in endothelial cells and improvement of glucose uptake 82 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…UCBs and peripheral blood mononuclear cell infusion therapy for patients with CP improved brain glucose metabolism, as observed in PET studies 73 , 80 . Autologous BM-MNC therapies for patients with ASD also showed improvements in glucose metabolism and various cognitive and behavioral symptoms such as eye contact, attention and concentration, hyperactivity, sitting tolerance, social interaction, stereotypical behavior, aggressiveness, communication, speech, command following, and self-stimulatory behavior, as well as improvement of glucose metabolism and motor function in patients with CP 47 , 81 . In 2020, we reported that angiogenesis is activated by BM-MNCs via gap junction–mediated cell–cell interaction soon after cell transplantation and that cell–cell interaction via gap junctions is the prominent pathway for the activation of angiogenesis in endothelial cells and improvement of glucose uptake 82 .…”
Section: Discussionmentioning
confidence: 91%
“…Dawson et al reported safe and feasible autologous UCBs infusion in young children with ASD, and several promising outcomes have been published 39 42 . Recently, UC-MSCs (umbilical cord–derived MSC) and bone marrow mononuclear cells (BM-MNCs) from individuals with ASD had favorable outcomes 43 49 ( Table 2 ). Fetal stem cells for individuals with ASD have shown favorable outcomes, albeit instigating an ethical dilemma regarding the use of fetal stem cells.…”
Section: Pathophysiologymentioning
confidence: 99%
“…O Transtorno do Espectro Autista (TEA) faz parte de um grupo de transtornos que comprometem a interação social e a comunicação, e afetam o comportamento do indivíduo através da presença de interesses e atividades restritas e repetitivas (Fogo, 2018;Sampaio, 2019;Sharma et al, 2020). De acordo com Queiroz e Mendes (2017) e Pavin et al (2019), o psiquiatra austríaco Leo Kanner, descreveu, pela primeira vez, o TEA em 1943.…”
Section: Introductionunclassified
“…Os sintomas mais comuns do autismo incluem baixo contato visual, dificuldade no entendimento de sinais não verbais, déficit na oratória e cognição, comportamentos repetitivos e dependência nas atividades diárias (Sharma et al, 2020). O transtorno é diagnosticado através de uma análise clínica-comportamental, seguindo critérios delimitados pelo Manual de Diagnóstico e Estatístico de Transtornos Mentais (DSM) ou pela Classificação Internacional de Doenças (CID) (Evangelho et al, 2021).…”
Section: Introductionunclassified
See 1 more Smart Citation